Chemical Composition, Antioxidant Properties and Hypocholesterolemic Effects of Differently Treated Roselle (Hibiscus Sabdariffa L.) Seeds - Khairul Ikram, Emmy Hainida (2006)
Roselle (Hibiscus sabdariffa L.) seeds, grown in Malaysia, were investigated. Effects of drying and boiling-drying of the seeds on the proximate analysis, minerals, amino acids content, vitamins, polyphenols and antioxidant activity were studied. Effect of dried roselle seeds (DRS), on lipid profiles of rats induced hypercholesterolemia was also conducted. Protein, lipids and dietary fiber were found to be high in all the seeds studied. Raw (RRS), dried (DRS) and boiled seeds (BRS) contained 57.3%, 9.9% and 9.8% moisture; 35.4%, 33.5% and 30.6% protein; 27.2%, 22.1% and 29.6% lipids; 2.3%, 13.0% and 4.0% available carbohydrate; 25.5%, 18.3%, and 19.2% total dietary fibers and 7.4%, 7.5% and 6.6% ash, respectively. There was a significant difference (p < 0.05) in protein, lipid and carbohydrate contents between treated and raw seeds. The predominant inorganic elements in the seeds were potassium (99 – 109 mg/100 g), magnesium (26 – 28 mg/100 g) and calcium (24 – 31 mg/100 g). The total dietary fiber of the seeds was considerable with the best ratio between soluble and insoluble ranging from 1.2 to 3.3. The study detected 17 essential and non-essential amino acids. The seeds were rich in lysine (14 – 15 g/100 g), arginine (30 – 35 g/100 g), leucine (15.4-18.6 g/100 g), phenylalanine (11 – 12 g/100 g) and glutamic acid (21 – 24 g/100 g). Sulphur containing amino acids, cystine (4.04 - 5.32 g/100 g protein) and methionine (2.50- 3.96 g/100 g protein) were the limiting amino acids of the seeds powder. Vitamin A content in DRS was (99.97 ± 2.99 μg retinol), followed by BRS (87.73 ± 0.49 μg retinol) and RRS (69.38 ± 0.36 μg retinol). BRS was found to contain the highest vitamin E value (0.19 ± 0.05 mg/g sample), followed by DRS (0.19 ± 3.20 mg/g sample) and RRS (0.07 ± 0.78 mg/g sample). Phenolic content for RRS, DRS and BRS were 105.6 ± 0.49, 39.6 ± 0.12 and 28.5 ± 0.61 mg/g sample, expressed as gallic acid equivalents (GAE), respectively. The total ferulic acids in RRS, BRS and DRS were 17.99 ± 0.29 mg/g, 1.96 ± 0.60 mg/g and 1.25 ± 0.62 mg/g samples, respectively. Methanolic extracts of DRS and BRS exhibited high antioxidant activity compared with ethanolic and n-butanolic extracts. β-carotene bleaching assay resulted in higher antioxidant activity in DRS compared to BRS powder in methanolic, ethanolic and n-butanolic extracts. In contrast, scavenging activitiy of BRS was found to be significantly higher than DRS. Significant differences (p < 0.05) were found among the following three extracts with values in the descending order of 80% methanol > absolute ethanol > n-butanol. In in-vivo study to determine the effect on lipid profile, 20 males Sprague-Dawley rats were randomly divided into 4 groups and fed with four different diets, respectively. The rats were fed with normal, hypercholesterol, hypercholesterol + 5% (w/w) DRS and hypercholesterol + 15% (w/w) DRS diets, respectively. Treatments were given for a total of 6 weeks. Results indicated that the addition of 5% and 15% DRS had significantly lowered (p<0.05) the total cholesterol (TC) and low density lipoprotein cholesterol (LDL-C) levels. However, there were no significant differences in triglyceride level. Furthermore, there was no significant increase in high density lipoprotein cholesterol (HDL-C) levels, with addition of DRS. In conclusion, findings indicated that the nutritional values of treated roselle seeds for human consumption are still considerable when compared to raw seeds. Nutritional benefits of raw and treated roselle seeds revealed that these seeds are promising with a high source of proteins, dietary fiber, essential amino acids and lipids. The present findings also indicated that the addition of 5% and 15% DRS showed to have a potential hypocholesterolemic effects.